Molecular mechanisms of template-independent RNA polymerization by tRNA nucleotidyltransferases - Tomita, Kozo; Yamashita, Seisueke (Frontiers in Genetics, 2014)
The universal 3'-terminal CCA sequence of tRNA is built and/or synthesized by the CCA-adding enzyme, CTP:(ATP) tRNA nucleotidyltransferase. This RNA polymerase has no nucleic acid template, but faithfully synthesizes the defined CCA sequence on the 3'-terminus of tRNA at one time, using CTP and ATP as substrates. The mystery of CCA-addition without a nucleic acid template by unique RNA polymerases has long fascinated researchers in the field of RNA enzymology. In this review, the mechanisms of RNA polymerization by the remarkable CCA-adding enzyme and its related enzymes are presented, based on their structural features.